Transbuccal delivery of betahistine dihydrochloride from mucoadhesive tablets with a unidirectional drug flow: in vitro, ex vivo and in vivo evaluation - El-Nabarawi MA; Ali AA; Aboud HM; Hassan AH; Godah AH (Dove Medical Press, 2016)
Mohamed A El-Nabarawi,1 Adel A Ali,2 Heba M Aboud,2 Amira H Hassan,2 Amany H Godah2 1Department of Pharmaceutics, Faculty of Pharmacy, Cairo University, Cairo, 2Department of Pharmaceutics, Faculty of Pharmacy, Beni-Suef University, Beni-Suef, Egypt Objective: Betahistine dihydrochloride (BH.2HCl), an anti-vertigo histamine analog used in the treatment of Ménière’s disease, undergoes extensive first-pass metabolism and suffers from short biological half-life. The aim of the present work was to develop and estimate controlled release mucoadhesive buccal tablets of BH.2HCl with a unidirectional drug flow to overcome this encumbrance. Methods: A direct compression method was adopted for preparation of the tablets using mucoadhesive polymers like guar gum, hydroxypropyl methyl cellulose K4M, sodium carboxymethyl cellulose and their combinations. The tablets were coated from all surfaces except one surface with a solution of 5% (w/v) cellulose acetate and 1% (w/v) dibutyl phthalate. Different permeation enhancers like 2% sodium deoxycholate, 2% sodium cholate hydrate (SCH) and 5% menthol were tested. Swelling index, ex vivo residence time, mucoadhesion strength, in vivo testing of mucoadhesion time, in vitro dissolution and ex vivo permeation were carried out. Furthermore, compatibility and accelerated stability studies were performed for the drug excipients. Finally, drug bioavailability of the BH.2HCl-optimized buccal mucoadhesive formulation was compared with that of the orally administered Betaserc® 24 mg tablet in six healthy male volunteers. Results: Formulation F10, which contained a combination of 35% guar gum and 5% sodium carboxymethyl cellulose, exhibited long adhesion time, high adhesion strength and diminished irritation to volunteers and showed zero-order release kinetics. SCH produced a significant enhancement in permeation of BH.2HCl across buccal mucosa. BH.2HCl-optimized buccal mucoadhesive formulation showed percentage relative bioavailability of 177%. Conclusion: The developed mucoadhesive tablets represent a promising alternative for the buccal delivery of BH.2HCl. Keywords: betahistine dihydrochloride, transbuccal delivery, unidirectional drug flow, permeation enhancer, relative bioavailability